PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP MINAT BELI SEPEDA MOTOR LISTRIK PADA DEALER CV JAYA TERANG DI SITUBONDO - Ediyanto, Ediyanto; Minullah, Minullah (Relawan Jurnal Indonesia, 2023)
The aim of this study to determine the effect of product quality, service quality and price variables partially on the variable buying interest of electric motorcycle on dealer CV Jaya Terang in Situbondo, to determine the effect of product quality, service quality and price variables simultaneously on variables interest in buying electric motorcycle on dealer CV Jaya Terang in Situbondo, to adhere to the influence of product quality, service quality and price variables that have a dominant influence on the interest of buying electric motorcycle on dealer CV Jaya Terang in Situbondo. The method used is quantitative. The results of the study are multiple linear regression equation Y = -1,104E-16 + 0,373X1 + 0,261X2 + 0,305X3 + e. Partially, product quality has a positive effect with tcount 4,112> ttable 1,985 sig value 0,000<0,05, service quality shows tcount value 3,479> ttable 1,985 sig value 0,001 <0,05, price indicates ttest value 3,420> ttable 1,985 sig value 0,001 <0,05. Simultaneously the product quality, service quality and price affect buying interest with a value of Fcount 31,509> Ftable 2,70. The most influential dominant variable in this study is product quality with a value of 4,112 greater than the service quality variable (X2) and the price variable (X3). Based on the coefficient of determination shows a value of 0,501 of the results means that all independent variables have a contribution of 50,1% to the dependent variable that has sufficient influence and the remaining 49,9% is influenced by other factors not included in the study.